Educational technologies regarding sports training of children with special educational needs - Ioan-Cosmin BOCA (Studii de Stiinta si Cultura, 2011)
The concept of Special Educational Needs (SEN), introduced by UNESCO in the '90s, determined the development of a constant concern of the specialists in physical education and sport to specify the special educational needs that require to be respected when addressing children presenting peculiarities of growth and development. Peculiarities of people with special educational needs in physical exercise practice require additional measures to those in general education. Through sport, children with special educational needs have the opportunity to experiment unprecedented life situations, to acquire a high degree of autonomy and have access to new cultural activities that encourage social integration.